Phenylalanine 4-Hydroxylase Contributes to Endophytic Bacterium Pseudomonas fluorescens’ Melatonin Biosynthesis - Jiao, Jian; Xia, Yan; Zhang, Yingli; Wu, Xueli; Liu, Chonghuai; Feng, Jiancan; Zheng, Xianbo; Song, Shangwei; Bai, Tuanhui; Song, Chunhui; Wang, Miaomiao; Pang, Hongguang (Frontiers in Genetics, 2021)
Melatonin acts both as an antioxidant and as a growth regulatory substance in plants. Pseudomonas fluorescens endophytic bacterium has been shown to produce melatonin and increase plant resistance to abiotic stressors through increasing endogenous melatonin. However, in bacteria, genes are still not known to be melatonin-related. Here, we reported that the bacterial phenylalanine 4-hydroxylase (PAH) may be involved in the 5-hydroxytryptophan (5-HTP) biosynthesis and further influenced the subsequent production of melatonin in P. fluorescens. The purified PAH protein of P. fluorescens not only hydroxylated phenylalanine but also exhibited l-tryptophan (l-Trp) hydroxylase activity by converting l-Trp to 5-HTP in vitro. However, bacterial PAH displayed lower activity and affinity for l-Trp than l-phenylalanine. Notably, the PAH deletion of P. fluorescens blocked melatonin production by causing a significant decline in 5-HTP levels and thus decreased the resistance to abiotic stress. Overall, this study revealed a possible role for bacterial PAH in controlling 5-HTP and melatonin biosynthesis in bacteria, and expanded the current knowledge of melatonin production in microorganisms.